Leadership : theory and practice - Northouse, Peter Guy (SAGE Publications, 2010)
With this text, Peter Northouse provides a description and analysis of a wide variety of different theoretical approaches to leadership, paying special attention to how each theory can be employed to improve leadership in practice.